A Prospective Comparative Study between the Software Models and Clinical Models of Clear Aligner Treatment (Orthodontic Journal of Nepal, 2019)
Introduction: The purpose of this prospective clinical study was to compare the three dimensional predicted software models with the stage clinical STL models and to evaluate the efficacy of tooth movement with clear aligners.Materials & Method: The sample size included 10 cases with mild anterior crowding treated with aligner therapy. The virtual model of the predicted tooth position was superimposed on the virtual model of the achieved tooth position at various stages over their stationary posterior teeth by using MeshLab software. The amount of tooth movement predicted was compared with the amount of tooth movement achieved.Result: The results of this study have shown that when a comparison was made on the basis of irregularity scores in both the groups, it was seen that the irregularity score was more in Clinical STL group at each stage such as 2.55 at T4, 1.65 at T6 and 1.0 at T8 whereas 2.0 at T4. 0.90 at T6 and 0.25 at T8 in the Software model group. Also, On comparing mean accuracy these three stages, the analysis of data showed the mean accuracy at T4 is 62.5%, mean accuracy at T6 is 68.8% and the mean accuracy at T8 is 78.1%.Conclusion: The predicted software models do not accurately reflect the patient’s tooth position .There is an overestimation by predicted software as compared to actual clinically achieved tooth position. There is a need of overcorrection to be built in the treatment planning stage itself and execution of the anticipated end result.